Sira Nabawiyya: Historiography of the Prophet Muhammad by Three Modern Writers - Abror, Muhamad; Rahma, Awalia (Buletin Al-Turas, 2024)
PurposeThis study aimed to compare the narratives of three modern historiographies of the Sirah Nabawiya. It explored differences and similarities of Raḫīq Al-Makhtūm, Muhammad: His Life Based on the Earliest Sources, and Membaca Sirah Nabi Muhammad dalam Sorotan Al-Qur'an dan Hadis-Hadis Sahih.MethodThis research employed a qualitative approach, adopting the historical method. The primary data were the most recent published editions of Al-Raḥīq Al-Makhtūm (2019) by Safiyurrahman Al-Mubarakfuri, Muhammad: His Life Based on the Earliest Sources (2006) by Martin Lings, and Membaca Sirah Nabi Muhammad dalam Sorotan Al-Qur’an dan Hadis-Hadis Sahih (2018) by M. Quraish Shihab.Results/FindingsThe research showed that each of these three books was written in a chronological style. Al-Raḥīq Al-Makhtūm and Membaca Sirah Nabi Muhammad dalam Sorotan Al-Qur'an dan Hadis-Hadis Sahih offered more detailed information compared to Muhammad: His Life Based on the Earliest Sources. In their historical analyses, each writer presented their respective perspectives and tendencies. Al-Mubarakfuri emphasized the comparison of historical data and explained the most valid source, while Lings presented the data in a friendly and approachable manner with no in-depth elaboration and personal analyses. Shihab's analysis, however, covered more complex issues beyond historiography, including verification, orientalist criticism, analysis of Quranic sources, and elaboration of moral values.ConclusionThese three works complied with the standard model of a chronological presentation of data and critical analysis, while maintaining a friendly and approachable tone through additional elaboration of perspectives. The authors maintained a balanced and objective approach according to their academic background.